Ethereum for Business : a plain-english guide to the Use Cases that Generate Returns from Asset Management to Payments to Supply Chains - Brody, Paul, ....- (Fayetteville : Epic books, 2023)
In Ethereum for Business, Paul Brody provides a plain English guide to doing business on the world's largest blockchain. The book covers an overview of Ethereum, business applications on Ethereum, and various advanced topics. Including case studies and examples from the world of Ethereum , Ethereum for Business is readable both lineary and by dipping in and out of chapters. The book is aimed at business executives who want to understand the potential of blockchain for solving real-world business problems, and readers with technical knowledge who want to understand the business use cases. Ethereum for Business covers topics such as data quality, efficiency, and decentralization in digital marketplaces, wallets, tokens, and smart contracts, privacy, scalability, supply chain management, trade finance, payments and asset transfers, and tokenomics. Brody argues that blockchain technology, particularly Ethereum, can transform the world of enterprise computing by enabling companies to model and manage assets, real or digital, thas exist off-chain. The result is a guide for implementation that contains key success metrics for enterprises considering blockchain.
Keywords: Blockchain